Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1136/rmdopen-2018-000799
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes and safety in patients undergoing synovial biopsy: comparison of ultrasound-guided needle biopsy, ultrasound-guided portal and forceps and arthroscopic-guided synovial biopsy techniques in five centres across Europe

Abstract: BackgroundWe present a European multicenter study, comparing safety data and patient-reported outcomes (PRO) from patients undergoing synovial biopsy using ultrasound-guided needle biopsy (US-NB), ultrasound-guided portal and forceps (US-P&F) or arthroscopic-guided (AG) procedures.ObjectivesTo describe safety and PRO data on joint indices of pain, stiffness and swelling before and after biopsy, procedural discomfort, joint status compared with before biopsy and willingness to undergo a second biopsy for each t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 17 publications
3
36
1
2
Order By: Relevance
“…There was no aggravation of joint symptoms or US synovitis following the procedure, similarly to what was previously reported in research‐driven biopsies (14,16). We hypothesize that the slight improvement in symptoms observed, also described in a different context (16), may be due to patient satisfaction with the biopsy procedure (as discussed above) and with the overall care and attention paid by the attending physician and biopsy operator. In fact, it has been shown that patient‐reported outcomes are affected by both the clinical outcome and patient satisfaction with the healthcare experience (29,30).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…There was no aggravation of joint symptoms or US synovitis following the procedure, similarly to what was previously reported in research‐driven biopsies (14,16). We hypothesize that the slight improvement in symptoms observed, also described in a different context (16), may be due to patient satisfaction with the biopsy procedure (as discussed above) and with the overall care and attention paid by the attending physician and biopsy operator. In fact, it has been shown that patient‐reported outcomes are affected by both the clinical outcome and patient satisfaction with the healthcare experience (29,30).…”
Section: Discussionsupporting
confidence: 88%
“…The tolerability profile of US‐guided synovial biopsies was excellent, in accordance with previous studies that formally assessed this technique in a research context (14–16). We provide evidence of the remarkable tolerability of this procedure in a clinical setting, in several joints, and in a different patient population.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Current studies are investigating whether synovial tissue analysis can be used as an instrument for personalised medicine in RA for diagnosis, prognosis and treatment stratification 1 2. The development of ultrasound-guided synovial biopsy (USGSB) as a minimally invasive, safe and well-tolerated technique for retrieving synovial tissue has accelerated research in synovial histopathology 3–5. RA synovial pathology is heterogeneous, with some patients exhibiting high levels of inflammation with infiltrating lymphoid follicles while others have a more diffuse inflammatory alterations, and some almost without inflammation 6.…”
Section: Introductionmentioning
confidence: 99%